Angiospermic flora of Runctia sal forest, Bangladesh. I. Liliopsida (Monocots) (Bangladesh Journal of Plant Taxonomy, 2009)
This paper presents 49 plant species belonging to 38 genera and 13 families of the division Liliopsida (monocots) from Runctia sal forest in Sherpur district, Bangladesh. The update nomenclature, habit, habitat and representative specimen have been provided for each species. Important synonyms and local names have also been furnished, wherever available. Keywords: Angiosperm; Monocots; Runctia sal forest. DOI: 10.3329/bjpt.v16i1.2750 Bangladesh J. Plant Taxon. 16(1): 83-90, 2009 (June)